Aspectos da infecção por Schistosoma mansoni ( SAMBON, 1907) em ovinos da raça Santa Inês - Jordana Costa Alves de Assis (2016)
The schistosomiasis is caused by trematode Schistosoma mansoni and is impactful on public health in many countries, particularly underdeveloped or under development countries. There are many researches regarding the infection in humans, however, there are only a few studies about the susceptibility of cattle to infection, such as in sheep. In Brazil, there is a gradual increase in the creation of these animals, such as Santa Ines breeds, due to its productivity and rusticity; without wool breeds is very established at the Brazilian northeast. The goal of this study is to evaluate aspects of susceptibility in Santa Inês sheep breeds to infection with S. mansoni, as well as clinical, haematological, parasitological and pathological in the period 0-255 days. The sheeps of this study were segmented into two groups of 05 animals free from infection (Control) and 05 dermally infected with 2,000 of S. mansoni cercariae (Infected). Clinical evaluation were performed to monitor variables such as weight and body condition score, in addition to the cardiovascular, respiratory, digestive system and mucosal staining analysis of the ocular conjunctive. Blood samples were collected to perform the hematological profile and kinetic profile of IgG antibodies. To analyze the parasitological parameters, diagnosis were performed through examinations by spontaneous sedimentation method and the four modified sieves method, as well as miracidia hatching methods, rectal mucosal curettage and antigen detection by rapid urine test. The sheeps were sacrificed at two intervals: the 135 dpi and 255 dpi. Body organs were examined. Moreover, it was preconized the perfusion of the viscera for parasite recovery vessels in the mesenteric and portal space and eggs in the tissues were recovered. As a result, on the clinical evaluation, there was loss of weight in the infected group of 15 to 75 dpi with compensatory growth, but not enough to match the control, as well as amorphous faeces. On the hematological analysis, lower levels in the red blood cells and variable increase in the total white blood count were found as well as differential of neutrophils in acute phase and an increase in the differential count of peripheral eosinophils cells of 75 to 195 dpi. The IgG kinetics showed high reactivity in the infected group, which shows a stronger humoral immune response in post postural acute when comparing the two titrations, concomitant with clinical and hematological findings. This can be used as a tool to immunodiagnostics of schistosomiasis in sheep. Regarding the parasitological parameters, the following results were obtained on diagnosis: (i) eggs or miracidia were observed in infected samples of breed sheep Santa Inês, however, (ii) Girão and Ueno (1982) technique have been validated for diagnosis of S. mansoni infection in ruminants hosts, (iii) rectal mucosas curettage were able to detect infection in sheep and (iv) the rapid test urine detected antigens, but slight traces that should be improved. In post mortem aspects, the pathology of the Santa Inês sheep infected was observed in the liver and the lung: (i) low frequency of typical granulomas formed around S. mansoni eggs and (ii) frequently focal, scattered, and nodular lesions, formed by extensive granulomas containing amorphous material wrapped in exudate inflammatory cells besides varying degrees of vascular connective neoformation. In recovered parasites at the mesenteric and portal vessels space, there was heterogeneity among the sheep with variations from 0.45 to 5.45%. Furthermore, the specimens of S. mansoni were smaller compared to those obtained in human and cattle infections. Thus, it is conclusive that breed sheep Santa Inês have no epidemiological importance in the transmission of S. mansoni since it does not eliminate eggs in faeces. However, these animals are susceptible to infection because there is parasitic development and female oviposition as well as clinical symptoms, hematologic and immunologic changes besides organ lesions at the liver and lungs consequent to the parasitism leading to losses in productivity due to infection.